The potentiation of Mangifera casturi bark extract on interleukin- 1β and bone morphogenic protein-2 expressions during bone remodeling after tooth extraction - Bayu Indra Sukmana; Theresia Indah Budhy; I Gusti Aju Wahju Ardani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: The main oral health problem in Indonesia is the high number of tooth decay. Tooth extraction is the treatment often received by patients who experience tooth decay and the wound caused by alveolar bone resorption. Bark of Mangifera casturi has been studied and proven to contain secondary metabolite which has the ability to increase osteoblast’s activity and suppress osteoclast’s activity. Purpose: The purpose of this study was to analyze interleukin-1 beta (IL-1β) and bone morphogenic protein-2 (BMP-2) activities during bone remodeling after Mangifera casturi’s bark extract treatment. Method: This study was laboratory experimental research with randomized post-test only control group design. The Mangifera casturi bark was extracted using 96% ethanol maceration and n-hexane fractionation. This study used 40 male Wistar rats which are divided into 4 groups and the tooth extraction was performed on the rats’ right mandible incisive tooth. The four groups consisted of 6.35%, 12.7%, 25.4% extract treatment group, and a control group. Wistar’s mandibles were decapitated on the 7th and 14th day after extraction. Antibody staining on preparations for the examination of IL-1β and BMP-2 expressions was done using immunohistochemistry. Result: There was a significant difference of IL-1β and BMP-2 expressions in 6,35%, 12,7%, and 25,4% treatment groups compared to control group with p<0.05. Conclusion: Mangifera casturi’s bark extract was able to suppress the IL-1β expression and increase the BMP-2 expression during bone remodeling after tooth extraction.